2019
DOI: 10.1007/s10548-019-00703-1
|View full text |Cite
|
Sign up to set email alerts
|

MEG Assessment of Expressive Language in Children Evaluated for Epilepsy Surgery

Abstract: Establishing language dominance is an important step in the presurgical evaluation of patients with refractory epilepsy. In the absence of a universally accepted gold-standard non-invasive method to determine language dominance in the preoperative assessment, a range of tools and methodologies have recently received attention. When applied to pediatric age, many of the proposed methods, such as functional magnetic resonance imaging (fMRI), may present some challenges due to the time-varying effects of epilepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 62 publications
(100 reference statements)
2
9
0
1
Order By: Relevance
“…In concordance with the literature, we observed a beta decrease after stimulus onset within the language-related regions within the dominant hemisphere (Hirata et al, 2004(Hirata et al, , 2010Fisher et al, 2008;Pang et al, 2011;Findlay et al, 2012;Foley et al, 2019;Youssofzadeh et al, 2020), and an increase within the non-dominant frontal and superior-parietal lobes (Sharma et al, 2021). The beta decrease was seen in controls between 300 and 800 ms and worked as the criterion to lateralize language in patients and controls.…”
Section: Megsupporting
confidence: 91%
See 2 more Smart Citations
“…In concordance with the literature, we observed a beta decrease after stimulus onset within the language-related regions within the dominant hemisphere (Hirata et al, 2004(Hirata et al, , 2010Fisher et al, 2008;Pang et al, 2011;Findlay et al, 2012;Foley et al, 2019;Youssofzadeh et al, 2020), and an increase within the non-dominant frontal and superior-parietal lobes (Sharma et al, 2021). The beta decrease was seen in controls between 300 and 800 ms and worked as the criterion to lateralize language in patients and controls.…”
Section: Megsupporting
confidence: 91%
“…Left: frontal ROI, middle: temporo-parietal ROI, right: other temporal areas. (Foley et al, 2019;Youssofzadeh et al, 2020), or applied clustercorrection to improve the sensitivity of statistics (Youssofzadeh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERD has been found during phonetic processing in typically developing children and adolescents, but not in children with developmental language impairments such as aphasia and dyslexia 29 . Indeed, low-beta (13–23 Hz) ERD is considered an oscillatory signature for expressive language in both children and adults 30 . Studies have found this ERD at perisylvian language networks as early as 650 ms and as late as 1200 ms post-stimulus presentation, which is thought to be locked to response timing 31 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is conceivable that ERS/ERD in each frequency band may have differential language processing functions. Furthermore, it has been reported that lateralising variations in ERD in the β band or the low γ band can function as a non-invasive index for estimating the language-dominant hemisphere during language tasks in patients with epilepsy and brain tumour [18][19][20] . Thus, cerebral oscillatory variations in MEG signal may be related to language function when detected in the context of a language-related task.…”
Section: Left Hemispheric α Band Cerebral Oscillatory Changes Correlamentioning
confidence: 99%